Students talent management through the sanggar-prestasi forum at mts negeri 2 maluku tengah - Muhamad Nasir Pariusamahu (12 Waiheru, 2025)
Student talent management through the Sanggar Prestasi concept at MTs Negeri 2 Maluku Tengah is an innovation in managing student talents and interests in one integrated forum. This study aims to determine the Sanggar Prestasi management concept in developing student talents. The approach used is descriptive qualitative through interviews with the Head of the Islamic schools, Deputy Head of Student Affairs, Sanggar Prestasi Coordinator, two mentors, two randomly selected students (wheel of names), and field observations and records. The study results show that since 2021, Sanggar Prestasi has hosted 20 extracurricular activities for 538 students. One teacher coordinates this studio as a planner, assistant, and reporter to the Head of Islamic schools. This program is fully supported by the Head of the Islamic schools, the development team, quality mentors, adequate facilities, and professional partners. Sanggar planning includes four stages: data collection and classification of activities, determination of coordinator and mentor decrees, and budget planning from BOS funds. The implementation of activities begins after effective hours, at 15.00–17.00 WIT, with routine guidance once a week per activity. The extracurricular schedule is divided into two groups, A and B. Evaluation is carried out in three models: monthly, semesterly, and annual year.